2014
DOI: 10.5603/fm.2014.0032
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and a proposed model of innervation of the human deltoid muscle: a pilot study

Abstract: Background:The deltoid muscle (DM) anterior fibres) and by pbAN (posterior fibres), and variation II, in which the spinal part did not have double innervation -the abAN innervation area covered only the acromial and clavicular parts, and the entire spinal part was supplied by pbAN. Both variations had a segmented arrangement of sub-branches reaching individual parts of the DM, which was particularly distinct in the clavicular Conclusions:The study confirmed the existence of a characteristic segmented inner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Because the clavicular part of PM develops from the same origin as deltoid muscle, it remains in close relation to the clavicular part of the deltoid; both parts are connected through fascial structures (deltopectoral fascia), especially in their distal part [46]. The clavicular part of the PM may also extend laterally on the clavicle as far as the deltoid muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Because the clavicular part of PM develops from the same origin as deltoid muscle, it remains in close relation to the clavicular part of the deltoid; both parts are connected through fascial structures (deltopectoral fascia), especially in their distal part [46]. The clavicular part of the PM may also extend laterally on the clavicle as far as the deltoid muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed two innervation patterns of the deltoid: by the axillary nerve or by a combination of the auxillary and the lateral pectoral nerves. The “classical” innervation pattern through the axillary nerve and its distribution in the deltoid muscle have been well defined by Stecco, Sakoma, Wysiadecki, Leechavengvongs and their colleagues (Leechavengvongs et al, ; Sakoma et al, ; Stecco et al, ; Wysiadecki et al, ). During our dissections, we confirmed the findings of those authors: the axillary nerve crossed the quadrangular space and sent anterior and posterior branches to three anatomical parts of the deltoid; the anterior branch supplied the clavicular and acromial portions, while the spinal head received innervation from the posterior branch (Figure 1a).…”
Section: Resultsmentioning
confidence: 96%
“…In contrast, when comparing the MM of the deltoid relative to that of the set of muscles that act on the glenohumeral joint, the humans had significantly higher values. This could be related to the important function of the deltoid in stabilizing the glenohumeral joint in humans (Rosso et al, 2014; Wysiadecki et al, 2014) since its MM creates pressure that may increase joint stability and thus decrease the upper translation of the humeral head when the upper limb is raised (Ackland et al, 2011; Kido et al, 2003; Ovesen & Nielsen, 1986). Nonetheless, the absolute and relative differences in the MM between humans and chimpanzees must be interpreted with caution when drawing conclusions about the function of the deltoid since these differences may well be partly the result of the older age of the human specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The three portions converge at the deltoid tuberosity, located in the middle region of the lateral surface of the humeral diaphysis (Gómez et al, 2020; Klepps et al, 2004). Functional studies in humans indicate that the deltoid is jointly involved in the elevation of the upper limb in the scapular plane (Inman et al, 1944; Klepps et al, 2004; Michilsens et al, 2010; Perry et al, 1989; Reddy et al, 2000; Rosso et al, 2014) and also ensures the stability of the glenohumeral joint (Ackland et al, 2011; Kido et al, 2003; Ovesen & Nielsen, 1986; Rosso et al, 2014; Wysiadecki et al, 2014). Electromyographic studies have shown that the CD acts as a flexor and medial rotator of the glenohumeral joint, the AD acts as an abductor of the glenohumeral joint, and the SD acts as an extensor and lateral rotator of the glenohumeral joint (Basmajian & de Luca, 1985; Gorelick & Brown, 2007; Gray & Standring, 2005; Levangie & Norkin, 2001).…”
Section: Introductionmentioning
confidence: 99%